RNA sequencing and integrative analysis reveal pathways and hub genes associated with TGFβ1 stimulation on prostatic stromal cells - Xiang, Peng; Du, Zhen; Wang, Mingdong; Liu, Dan; Yan, Wei; Hao, Yongxiu; Liu, Yutong; Guan, Di; Ping, Hao (Frontiers in Genetics, 2022)
Objective: Benign prostatic hyperplasia (BPH) is the most common urological disease in elderly men. The transforming growth factor beta 1 (TGFβ1) plays an important role in the proliferation and differentiation of BPH stroma. However, it is not yet clear which important pathways and key genes are downstream of TGFβ1 acting on prostatic stromal cells. Methods: GSE132714 is currently the newer, available and best high-throughput sequencing data set for BPH disease and includes the largest number of BPH cases. We examined TGFβ1 expression level in BPH and normal prostate (NP) by analyzing GSE132714 data set as well as carrying out immunohistochemistry of 15 BPH and 15 NP samples. Primary prostatic stromal cells (PrSCs) were isolated from five fresh BPH tissues. RNA sequencing and bioinformatics analysis were used to reveal important pathways and hub genes associated with TGFβ1 stimulation on PrSCs. Results: TGFβ1 was upregulated in BPH stroma than in NP stroma. A total of 497 genes (244 upregulated and 253 down-regulated) were differentially expressed in PrSCs with and without TGFβ1 stimulation. Gene Ontology revealed that differentially expressed genes (DEGs) were mainly enriched in progesterone secretion, interleukin-7 receptor binding and CSF1-CSF1R complex. Wnt signaling pathway, PI3K−Akt signaling, JAK−STAT signaling pathway and Hippo signaling pathway were screened based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. FN1, SMAD3, CXCL12, VCAM1 and ICAM1 were selected as hub genes according to the degree of connection from the protein-protein interaction (PPI) network. Conclusion: This study sheds some new insight on the role of TGFβ1 in BPH stroma, and provides some clues for the identification of potential downstream mechanisms and targets.